The theory of caritative caring: Katie Eriksson’s theory of caritative caring presented from a human science point of view - Näsman, Yvonne (Nursing Philosophy, 2020)
Abstract The Finnish nursing theorist Katie Eriksson's (1943–2019) theory of caritative caring represents a non‐medical paradigm concerning the phenomena of nursing. The aim of this article was to present an oversight of the development of Eriksson's theory of caritative caring from a human science point of view. The historical development of the theory is outlined, combined with a brief overview of its philosophical connections, its impact on contemporary caring science research and its implications for nursing care. Caring science is considered a human science in the Nordic tradition, as it is deeply rooted in basic issues of human life and existence. The key ideas of Eriksson's theory of caritative caring are linked to the metaparadigm concepts of human being, health and suffering, caring and environment. All of these are permeated with the ethos of caritative caring, that is, the caritas thought of human love and mercy, and the honouring of the absolute dignity of human beings. Epistemologically, Gadamer is the most influential philosopher when it comes to the theory of caritative caring. Eriksson's theory is used in, for example, intercultural caring, caring for patients suffering from addiction, the importance of aesthetic surroundings, providing ethically good care for older people and mothers as patients in psychiatric care. In these fields of research, Eriksson's ideas of ethics, caring and suffering are highlighted in various clinical contexts. Beyond the areas of nursing care in which Eriksson's work has been cited and developed, there are at least two areas that have been actively enhanced by her works: the field of leadership and education for nursing teachers. According to Eriksson, it is momentous to ponder scientific results as not limited to empirically strengthened, randomized outcomes. Part of making the results of scientific work evident is up to the individual nurses and their being in the world .